Evaluation of the management artistic gymnastics management in Kediri City - Denes Ananda Arfiantari; Moh Nur Kholis; Puspodari Puspodari; Budiman Agung Pratama (Sriwijaya Journal of Sport, 2022)
This study will focus on the management of the Persani Artistic Gymnastics Kediri which aims to the out more about what management does in managing the Persani. This study will also examine training programs, evaluation, and management of facilities and infrastructure. This study used a qualitative descriptive approach, qualitative descriptive research only used one variable, the researchers conducted research with the procedures for collecting data from observations, interviews, and documentation to coaches, coaches, athletes, and athletes' parents. researchers will describe management at Persani Artistic Gymnastics Kediri in 2022. The results of this study are based on the results of the data obtained that management at Persani artistic gymnastics Kediri City in 2022 has been doing well. that in the management function efforts there is planning, organizing, implementing, and monitoring that has been carried out properly. The management function, training program, achievement development, and evaluation program have been carried out and implemented well.